Oil and Gas Conference. Day 1. Tape 02. - Memorial University of Newfoundland. Extension Service (MUN Extension Service, 1979)
Opening address by Premier Brian Peckford (importance of conference, history of offshore, jurisdiction); Question session (port facilities, agriculture, Federal government).